Preschoolers’ emotional management: A survey of 164 Chinese children - Mi Yu; Zanariah Ahmad (Environment and Social Psychology, 2025)
Emotional management is one of the core skills that preschoolers need in their social and academic development. Nevertheless, the present-day Chinese early childhood education does not have systematic inclusion in the development of emotional competencies, which is why it is necessary to study the developmental trends and educational deficiencies through an empirical approach. This paper explored developmental patterns of emotional management skills in four domains, recognition and understanding, expression, regulation, and application of emotional management skills among Chinese preschoolers to guide evidence-based curriculum development. A mixed-method design surveyed 164 children (ages 3-6) from six intact classes in Huaibei City, employing teacher-rated questionnaires and semi-structured interviews. Data analysis included descriptive statistics, one-way ANOVA with Tukey’s post-hoc tests, and thematic analysis of interview transcripts. Children demonstrated moderate performance across dimensions (M=2.75-2.90). Significant age-related improvements emerged in emotion recognition (F(5,158)=7.002, p<0.001), expression (F(5,158)=3.452, p=0.005), and regulation (F(5,158)=4.320, p=0.001), with large classes consistently outperforming younger peers. However, emotion application showed no significant age differences (F(5,158)=2.193, p=0.058), revealing a critical transfer gap between strategy knowledge and practical implementation. The results show the necessity of well-organized interventions with a focus on knowledge-to-practice transfer based on situational simulation, structured role-play, and contextualized emotional strategy rehearsal. Instead of teaching cognitive strategies, education programs ought to emphasize the process of closing the knowing-doing gap.